2016
DOI: 10.1111/ijcp.12843
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dapoxetine in treatment of premature ejaculation: an evidence-based review

Abstract: Dapoxetine is the only effective and safe available on-label oral treatment for PE, and its use can result in better quality of life for the patient and their sexual partner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 56 publications
1
28
0
3
Order By: Relevance
“…Pharmacological investigations have shown that dapoxetine is a potent inhibitor of the 5‐HT transporter, that its pharmacokinetics are not affected by age, ethnicity or dosing frequency (with doses of 30 and 60 mg) and that “on‐demand” usage is effective (Andersson, Mulhall, & Wyllie, ), making dapoxetine a novel effective treatment modality for PE (Simsek et al., ). The results of several studies show that dapoxetine can improve the symptoms of PE, prolong IELT and increase sexual satisfaction (Simsek et al., ; Russo et al., ). In our study, therefore, patients with PPE received dapoxetine (30 mg) treatment of at least 12 tablets (on demand) before a re‐check.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological investigations have shown that dapoxetine is a potent inhibitor of the 5‐HT transporter, that its pharmacokinetics are not affected by age, ethnicity or dosing frequency (with doses of 30 and 60 mg) and that “on‐demand” usage is effective (Andersson, Mulhall, & Wyllie, ), making dapoxetine a novel effective treatment modality for PE (Simsek et al., ). The results of several studies show that dapoxetine can improve the symptoms of PE, prolong IELT and increase sexual satisfaction (Simsek et al., ; Russo et al., ). In our study, therefore, patients with PPE received dapoxetine (30 mg) treatment of at least 12 tablets (on demand) before a re‐check.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, no adverse effects of the PFM rehabilitation protocol were identified, compared to other medical therapies such as gastrointestinal symptoms (nausea and diarrhea) and dizziness and headaches, which have been associated with the use of dapoxetine. 22,23 In addition, the long-term effects of dapoxetine on reproductive functions should be cleared as some recent data demonstrated its negative impact on fertility. 24 To the best of our knowledge, the present study has the longest follow-up period (36 months) reported to date for any intervention for PE.…”
Section: Discussionmentioning
confidence: 99%
“…Сегодня дапоксетин считается единственным эффек тивным и безопасным пероральным препаратом лечения ПЭ, использование которого может улучшить качество жизни пациента и сексуального партнера [56][57][58][59].…”
unclassified